Legume Alternative Oxidase Isoforms Show Differential Sensitivity to Pyruvate Activation - Sweetman, Crystal; Selinski, Jennifer; Miller, Troy K.; Whelan, James; Day, David A. (Frontiers in Plant Science, 2022)
Alternative oxidase (AOX) is an important component of the plant respiratory pathway, enabling a route for electrons that bypasses the energy-conserving, ROS-producing complexes of the mitochondrial electron transport chain. Plants contain numerous isoforms of AOX, classified as either AOX1 or AOX2. AOX1 isoforms have received the most attention due to their importance in stress responses across a wide range of species. However, the propensity for at least one isoform of AOX2 to accumulate to very high levels in photosynthetic tissues of all legumes studied to date, suggests that this isoform has specialized roles, but we know little of its properties. Previous studies with sub-mitochondrial particles of soybean cotyledons and roots indicated that differential expression of GmAOX1, GmAOX2A and GmAOX2D across tissues might confer different activation kinetics with pyruvate. We have investigated this using recombinantly expressed isoforms of soybean AOX in a previously described bacterial system (Selinski et al. 2016. Physiologia Plantarum 157, 264-279). Pyruvate activation kinetics were similar between the two GmAOX2 isoforms but differed substantially from those of GmAOX1, suggesting that selective expression of AOX1 and 2 could determine the level of AOX activity. However, this alone cannot completely explain the differences seen in sub-mitochondrial particles isolated from different legume tissues and possible reasons for this are discussed.